Multiscale analysis and experimental validation of the effective elastic modulus of epoxy-dioctahedral phyllosilicate clay composite. Issue 6 (June 2020) - Daramola, O.O.; Olajide, J.L.; Adediran, A.A.; Adewuyi, B.O.; Ayodele, T.T.; Desai, D.A.; Sadiku, E.R.
Abstract: In this research, developed finite element codes were used to study the effective elastic modulus and stress-strain distribution profiles of epoxy resin filled with 6 wt. % microparticles of kaolinite. The random distribution of the particles was microstructurally regenerated with Digimat MSC software and random sequential algorithm codes in epoxy matrix. Stochastic representative volume element models of the composites were developed and analyzed under periodic boundary conditions. For validation, the predicted result by finite element analysis was compared with that of Mori-Tanaka's mean field homogenization scheme, selected micromechanical models and experiment. All the results indicated that 6 wt. % of kaolinite microparticles can improve the elastic modulus and load-bearing capacity of epoxy resin with <5 % error between predicted and actual results. The microstructure, phase identification and chemical characterization of the composite were also studied with scanning electron microscopy, x-ray diffraction spectroscopy and energy-dispersive x-ray spectroscopy, respectively. In addition, the particle size and distribution of the kaolinite in the epoxy matrix were experimentally investigated. Abstract : Materials Science; Epoxy resin; Kaolinite Inclusion; Layered Silicate Mineral; Finite Element Modeling; Polymer composites.